'Myxoedema madness' with Capgras syndrome and catatonic features responsive to combination olanzapine and levothyroxine. (9th September 2016) - Shlykov, Maksim A; Rath, Swapnil; Badger, Alison; Winder, Gerald Scott
Abstract : We present the case of an elderly woman with hypothyroidism and no psychiatric history who presented with new onset of psychosis, paranoia, catatonic features and Capgras syndrome (CS). This case illustrates the spectrum of neuropsychiatric symptoms that may accompany hypothyroidism and the importance of considering thyroid dysfunction as a primary contributor to severe psychiatric symptoms, especially in previously stable patients. We demonstrate the effectiveness of combination levothyroxine and olanzapine, with its favourable cardiac profile, in the treatment of myxoedema madness. Antipsychotics can be weaned once psychiatric symptoms resolve and hormone levels are stabilised.